Effect of ripening stage on the development of the microbial community during spontaneous fermentation of green tomatoes. (27th November 2013) - Paramithiotis, Spiros; Kouretas, Konstantinos; Drosinos, Eleftherios H
Abstract BACKGROUND Spontaneous fermentation of plant‐derived material is mainly performed on a small scale, with the exception of fermented olives, cucumbers, sauerkraut and kimchi, which have met worldwide commercial significance. RESULTS This study of spontaneous fermentation of green tomatoes at different stages of ripening revealed a significant effect on the growth kinetics of lactic acid bacteria and the final pH value. Leuconostoc mesenteroides dominated spontaneous fermentation when the initial pH value ranged from 3.8 to 4.8 whereas at higher pH values (4.9–5.4) it co‐dominated with Leu. citreum and Lactobacillus casei. Application of RAPD‐PCR and rep‐PCR allowed differentiation at sub‐species level, suggesting a microbial succession at that level accompanying the respective at species level. CONCLUSION Ripening stage affected the development of the micro‐ecosystem through the growth of lactic acid bacteria and concomitant pH value reduction; however, the outcome of the fermentation was only marginally different. © 2013 Society of Chemical Industry